Correlations of Metabolic Components with Prostate Volume in Middle-Aged Men Receiving Health Check-Up - Yang, Teng-Kai (PLoS One, 2016)
OBJECTIVES: To investigate the impact of metabolic components and body composition indices on prostate volume (PV) in a population of middle-aged men receiving health check-ups. METHODS: Six hundred and sixteen men receiving health assessments were stratified to large and small prostates based on the cut-off of median PV. Their demographic data, health history, and international prostate symptoms scores (IPSS) were collected. Metabolic components and body composition indices were compared between subjects with large and small prostates. Moreover, the correlations between these parameters and PV were analyzed by multivariate logistic regression. RESULTS: The median PV was 27 mL and mean age was 54.8 years. Subjects with large PV were older (56.5 vs. 52.7 years) and had higher serum prostate specific antigen (PSA) level (1.73 vs. 0.96 ng/mL), higher IPSS score (8.37 vs. 6.16), and higher body fat, body mass, and waist circumference (all p<0.05). In multivariate analysis, age (OR, 2.45; 95%CI, 1.74–3.45), serum PSA (OR, 2.75; 95%CI, 1.96–3.86), waist circumference (OR, 1.45; 95%CI, 1.02–2.07), fatness (OR, 1.47; 95%CI, 1.04–2.09), and body fat mass (OR, 1.43; 95%CI, 1.00–2.03) were significantly correlated with PV of study subjects. In subgroup analysis, raised waist circumference (OR, 1.89; 95%CI, 1.00–3.59) was the independent predictor of PV in subjects with bothersome lower urinary tract symptoms. CONCLUSIONS: Several metabolic components and body composition indices are significantly associated with PV of middle-aged men, including raised waist circumference, fatness, and body fat mass. Raised waist circumference is the only independent predictor of PV in middle-aged men with bothersome LUTS.